Systemic analysis identifying PVT1/DUSP13 axis for microvascular invasion in hepatocellular carcinoma. (16th December 2022) - Su, Renyi; Zhang, Huizhong; Zhang, Lincheng; Khan, Abdul Rehman; Zhang, Xuanyu; Wang, Rui; Shao, Chuxiao; Wei, Xuyong; Xu, Xiao
Abstract: Background: Microvascular invasion (MVI) is an independent detrimental risk factor for tumor recurrence and poor survival in hepatocellular carcinoma (HCC). Competitive endogenous RNA (ceRNA) networks play a pivotal role in the modulation of carcinogenesis and progression among diverse tumor types. However, whether the ceRNA mechanisms are engaged in promoting the MVI process in patients with HCC remains unknown. Methods: A ceRNA regulatory network was constructed based on RNA‐seq data of patients with HCC from The Cancer Genome Atlas (TCGA) database. In total, 10 hub genes of the ceRNA network were identified using four algorithms: "MCC, " "Degree, " "Betweenness, " and "Stress." Transcriptional expressions were verified by in situ hybridization using clinical samples. Interactions between ceRNA modules were validated by luciferase reporting assay. Logistic regression analysis, correlation analysis, enrichment analysis, promoter region analysis, methylation analysis, and immune infiltration analysis were performed to further investigate the molecular mechanisms and clinical transformation value. Results: The ceRNA regulatory network featuring a tumor invasion phenotype consisting of 3 long noncoding RNAs, 3 microRNAs, and 93 mRNAs was constructed using transcriptional data from the TCGA database. Systemic analysis and experimentally validation identified a ceRNA network (PVT1/miR‐1258/DUSP13 axis) characterized by lipid regulatory potential, immune properties, and abnormal methylation states in patients with HCC and MVI. Meanwhile, 28 transcriptional factors were identified as potential promotors of PVT1 with 3 transcriptional factors MXD3, ZNF580, and KDM1A promising as therapeutic targets in patients with HCC and MVI. Furthermore, miR‐1258 was an independent predictor for MVI in patients with HCC. Conclusion: The PVT1/DUSP13 axis is significantly associated with MVI progression in HCC patients. This study provides new insight into mechanisms related to lipids, immune phenotypes, and abnormal epigenetics in oncology research. Abstract : In this study, we identified a PVT1/miR‐1258/DUSP13 ceRNA axis characterized with lipid regulatory potential, immune properties, and abnormal methylation states in patients with HCC and MVI. Furthermore, miR‐1258 was an independent predictor for MVI in patients with HCC.